Estimating Clinical Manifestations in Cell Biology Teaching is a Suitable Active Element for Teaching Beginning Medical Students - Pavel Dvorak; Zbynek Tonar (Journal of Medical Education and Curricular Development, 2026)
Objective Cell biology courses in medical education often emphasize molecular detail without sufficient clinical integration, which can reduce student motivation and hinder application of knowledge. Embedding diagnostic reasoning into basic science teaching may enhance engagement and relevance. We developed short, task-based exercises in which students are actively encouraged to infer potential clinical symptoms of genetically determined diseases from cellular mechanisms. Methods Each task followed three steps: (1) introduction to a specific cellular process, (2) guided prediction of clinical manifestations resulting from dysfunction of key proteins, and (3) verification of hypotheses through published literature. Tasks were implemented into first-year medical student seminars of Medical Biology in both face-to-face and online formats. Evaluation was based on assessments by experienced teachers and a student questionnaire at the end of the course. Results Two illustrative tasks were presented: role of adhesion proteins in leukocyte extravasation, linked to leukocyte adhesion deficiency syndromes, and sarcolemma–cytoskeleton interactions, associated with various muscular dystrophies. Teachers as well as students consistently rated the tasks positively in surveys conducted. Better understanding of the connection between cellular mechanisms and clinical symptoms, greater confidence in diagnostic reasoning, and an increased ability to search and interpret scientific literature were reported. Based on the evaluation, modifications to the learning outcomes were proposed to place greater emphasis on the ability to draw conclusions from cellular processes. Conclusion Integrating short, clinically anchored exercises into cell biology teaching provides an effective means of activating student learning and fostering early diagnostic reasoning. This approach strengthens the perceived relevance of basic science, supports critical thinking, and offers a scalable model for enhancing preclinical medical curricula.